2023
DOI: 10.1002/ncp.10952
|View full text |Cite
|
Sign up to set email alerts
|

Prone position, time to reach nutrition target, and energy/protein achievement rate on the seventh day of intensive care unit stay in patients with COVID‐19: A cohort study

Abstract: Background: We aimed to evaluate the mean time to reach the energy (EAR) and protein (PAR) achievement rate among patients with coronavirus disease 2019 (COVID-19) who did or did not undergo prone position (PP) therapy in the first week of their stay in the intensive care unit (ICU), and the interaction of these nutrition therapy indicators on the association between PP and clinical outcomes. Methods: This cohort study used retrospective data collected from medical records of patients with COVID-19 admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…Protein and energy adequacy in our study was less than three other observational studies, which were conducted in critically ill patients with COVID‐19 in the United Kingdom, 37 Brazil, 38 and Mexico 39 . However, nutrition adequacy in our study was greater than the reported means for Australian populations 24 .…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Protein and energy adequacy in our study was less than three other observational studies, which were conducted in critically ill patients with COVID‐19 in the United Kingdom, 37 Brazil, 38 and Mexico 39 . However, nutrition adequacy in our study was greater than the reported means for Australian populations 24 .…”
Section: Discussioncontrasting
confidence: 84%
“…3 Various strategies to achieve nutrition targets have been attempted in the critically ill, including volume-based feeding strategies, 23 bolus feeding, 35 and using a very high-protein liquid formula. 36 The first two strategies, although beneficial at augmenting protein provision, require additional nursing time or a change to the Protein and energy adequacy in our study was less than three other observational studies, which were conducted in critically ill patients with COVID-19 in the United Kingdom, 37 Brazil, 38 and Mexico. 39 However, nutrition adequacy in our study was greater than the reported means for Australian populations.…”
Section: Discussionmentioning
confidence: 77%